Ecología de la fauna chaqueña. Una revisión. - Bucher, Enrique H. (Ecosur, 2023)
The present status of knowledge about the Chaco fauna is reviewed. The main points considered inelude: The environment. Regional división. The fauna: mammals, birds, reptiles, anurans and invertebrates. Pattems of species diversity. Adaptations of the Chaco animáis. Key processes. The following relevant processes are considered in detail: edaphic inñuence of ants, termites and mammals; decomposers and reducers; pattems of herbivory, particularly the importance of leaf-cutting ants as primary consumers; and the impact of human activity on the Chaco fauna.